Peran Stakeholder Internal Dalam Upaya Peningkatan Mutu Pendidikan Di SMP Negeri 1 Wonosalam Jombang - Sunardi Sunardi; Muallil Muallil (LP3M IAI Al Urwatul Wutsqo Jombang, 2023)
This study aims to analyze the role of internal stakeholders in efforts to improve the quality of education at SMP Negeri 1 Wonosalam, Jombang. The research method used is qualitative research with a case study approach. Data was collected through observation, interviews, and the analysis of related documents. The respondents to this study were teachers, principals, and administrative staff at SMP Negeri 1 Wonosalam, Jombang. The results of the study show that internal stakeholders play an important role in efforts to improve the quality of education at SMP Negeri 1 Wonosalam, Jombang. Teachers have a key role in providing quality teaching, developing relevant curricula, and managing effective and innovative learning. The principal is responsible for leading and managing the school, facilitating teacher professional development, and creating a conducive school climate for learning. Administrative staff plays a role in supporting the smooth administration and management of the school. Collaboration between internal stakeholders is also important in improving the quality of education. Teachers work together with school principals and administrative staff in developing educational programs, monitoring and evaluating learning, and making decisions related to quality improvement. Good communication between internal stakeholders is also a key factor in overcoming challenges and achieving common goals. This research provides a better understanding of the role of internal stakeholders in efforts to improve the quality of education at SMP Negeri 1 Wonosalam, Jombang. The implications of this research are expected to provide input for education policymakers, school principals, teachers, and administrative staff to improve the quality of education by optimizing the role of internal stakeholders